Model transformation: the heart and soul of model-driven software development - Sendall, S.; Kozaczynski, W. (IEEE software, 2003)
The model-driven approach can increase development productivity and quality by describing important aspects of a solution with human-friendly abstractions and by generating common application fragments with templates. This article examines different approaches to model transformations and recommends desirable language characteristics for describing them.